Cyana fossi, a new species from Vietnam (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Volynkin, Anton V.; Ivanova, Maria S. (Zootaxa, 2021)
Cyana Walker, 1854 is one of the most species-rich Erebiidae genera within the tribe Lithosiini Billberg of the subfamily Arctiinae Leach. The genus is widespread from Sub-Saharan Africa and Madagascar through southern and eastern Asia to New Guinea and Australia with a diversity hot spot in South East Asia. A striking species with contrasting red and orange wing pattern, C. bellissima (Moore, 1878) was described from northern India and recorded from the Himalayas, China and Indochina (Fang 2000; Černý & Pinratana 2009; Singh et al. 2020). Another closely related species, C. stresemanni (Rothschild, 1936) (= bellissima inouei Kishida, 1993) is distributed in the Peninsular Malaysia (Rothschild 1936; Kishida 1993; Bucsek 2012). During examination of extensive unsorted Lithosiini materials housed in the MWM/ZSM and the private collection of the senior author, a series of peculiar specimens from southern Vietnam provisionally identified as ‘C. bellissima’ was found. These specimens, however, display certain external differences from other populations of C. bellissima and C. stresemanni, suggesting the presence of a further taxon related to C. bellissima. The examination of the male and the female genitalia of the southern Vietnamese specimens has confirmed their specific distinctness and they are described in this paper as a new species.